Niobium-tantalum oxide solid solution material and preparation method thereof
The (Nb,Ta)(C,N) carbonitride was used as a precursor to prepare (NbxTa1-x)2O5 oxide solid solution powder, which solved the instability of existing dielectric materials in high temperature and high pressure environments. and the problem of unadjustable dielectric performance, it realizes efficient and environmentally friendly dielectric material preparation, suitable for high-performance dielectric capacitors.
Patent Information
- Application Number
- CN202411735850.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing dielectric materials are unstable in high temperature and high voltage environments and their dielectric properties are unadjustable, limiting their application in high-performance dielectric materials.
(Nb,Ta)(C,N) carbonitride is used as the precursor, and (NbxTa1-x)2O5 oxide solid solution powder is prepared by one-step oxidation method, achieving efficient preparation of the material, which is high-temperature and high-pressure breakdown resistance. and adjustable dielectric properties.
Simplify the production process, reduce energy consumption, avoid the use of organic solvents, improve the environmental protection and production safety of materials, significantly improve the feasibility of industrial applications, and show excellent dielectric performance in high-performance dielectric materials .
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a niobium tantalum oxide solid solution (Nb x Ta 1-x )2O5) powder is suitable for electrolyte capacitor material. Background Art
[0002] Dielectric capacitors are widely used in communications, computers, medical and military equipment due to their excellent performance in power regulation, energy density improvement and charge efficiency optimization. In addition, these materials also support renewable energy technologies, such as efficient energy conversion and storage in solar and wind energy systems. Dielectric materials are a class of insulating materials with high resistivity and high dielectric constant. They store and release electrical energy in an electric field through charge polarization, and therefore play a key role in the manufacture of dielectric capacitors and a variety of electronic and electrical devices. Currently, aluminum oxide (Al2O3) and lead lanthanum zirconium titanate (Pb 1-y La y )(Zr x Ti 1-x )O3, abbreviated as: PLZT) is the most commonly used dielectric material. Al2O3 is well known for its superior electrical insulation properties and high temperature stability, but it also has some defects that cannot be ignored. First, in a humid environment, Al2O3 is prone to electrochemical reactions, resulting in a decrease in its electrical performance. Especially in applications that require long-term stability in a humid environment, this reaction may cause instability in the material performance. Secondly, the dielectric constant of Al2O3 is relatively low, usually between 9-10, which limits its use in applications with high dielectric constant requirements, such as in high-K dielectric layers and certain specific capacitors. In addition, the dielectric properties of Al2O3 are almost non-adjustable, which has become a major disadvantage under the current technological development trend, especially in the design and manufacture of tunable electronic devices. In contrast, PLZT is a highly functional dielectric material, especially suitable for capacitors and other electronic devices. The dielectric properties can be adjusted by adjusting the ratio of lead, lanthanum, zirconium and titanium. This adjustability makes PLZT very suitable for the field of modern electronic technology that requires high flexibility. However, PLZT also has significant disadvantages. First, its breakdown voltage (105 kV / mm) is relatively low, which may cause material failure in high-voltage applications, thus limiting its application in high-power electronic devices. In addition, PLZT may require regular maintenance during use to maintain performance, especially in long-term operation or extreme environments, which increases the complexity and cost of subsequent maintenance. More importantly, the lead-containing ingredients bring potential environmental and health issues, which requires additional safety measures, further increasing the cost and complexity of the application.
[0003] With the continuous progress in the fields of power electronics, communications, automobiles, consumer electronics, and aerospace, the performance requirements for dielectric materials, especially breakdown voltage, adjustable performance, and high temperature stability, are also increasing. In the field of power electronics, dielectric materials need to prevent failures during high voltage operation, while in the battery management system of automobiles, especially electric vehicles, these materials must maintain performance and safety in high temperature environments. For example, capacitors in electromagnetic guns and vehicle protection systems need to have high breakdown strength (300-1000 kV / mm), fast discharge capability (10 -6 Seconds or less) and high power density, while maintaining stability at high temperatures exceeding 150°C to meet stringent environmental and performance requirements. Therefore, it is particularly important to develop dielectric materials that are resistant to high temperature, high voltage breakdown, and have high tunability.
[0004] In the search for materials that can withstand high voltage and high temperature and have adjustable dielectric properties, tantalum oxide (Ta2O5) and niobium oxide (Nb2O5) have attracted much attention due to their high melting points (Ta2O5: 1872℃, Nb2O5: 1512℃) and excellent high temperature resistance. These two materials not only exhibit extremely high breakdown strength (350 kV / mm for Ta2O5 and 500 kV / mm for Nb2O5), making them particularly important in military and automotive electronic devices, but their large band gaps (3.4eV for Nb2O5 and 3.8 eV for Ta2O5) also ensure stable operation of the equipment in extreme environments. Although these materials offer higher dielectric constants (Ta2O5: 42, Nb2O5: 77), the non-adjustability of their dielectric properties limits their flexibility in advanced applications that need to adapt to different electronic environments. To address this problem, (Nb2O5) was developed. x Ta 1-x )2O5 solid solution, the dielectric properties can be adjusted by adjusting the ratio of Nb to Ta. It is reported that the equimolar ratio of (Ta 0.5 Nb 0.5 )2O5 solid solution has a dielectric constant of about 54, which conforms to the linear law ((42+77) / 2=59.5), thus enhancing the application potential of the material. x Ta 1-x )2O5 solid solution not only inherits the high temperature and high pressure resistance characteristics of Ta2O5 and Nb2O5, but also shows broad application prospects in the field of high-performance dielectric materials through adjustable dielectric properties.
[0005] Since both Ta2O5 and Nb2O5 have orthorhombic crystal structures and have similar lattice constants and metal atomic radii, they can theoretically form solid solutions. Although the lattice parameters and unit cell volumes of these two materials are different, they both maintain the basic characteristics of the orthorhombic crystal system, where α = β = γ = 90.0°. Specifically, the lattice parameters of Ta2O5 are a = 6.198 Å, b = 40.29 Å, c = 3.888 Å, and the unit cell volume is 970.9 ų; while the lattice parameters of Nb2O5 are a = 6.168 Å, b = 29.312 Å, c = 3.936 Å, and the unit cell volume is 711.6 ų. Therefore, (Nb x Ta 1-x )2O5 oxide solid solution maintains an orthorhombic crystal structure with lattice parameters and unit cell volume between the two. The solid solution is composed of NbO6 / TaO6 octahedra, which are connected by shared corners to form a three-dimensional network. On the ab plane, the two-dimensional Nb2O3 / Ta2O3 layers are connected to adjacent layers by coordinated oxygen atoms along the c-axis, forming a linear chain structure of -Nb / Ta-O-Nb / Ta-O-Nb / Ta-. The compatibility of this crystal structure and the similarity of lattice parameters are the key to the formation of a stable solid solution of these two materials, making (Nb x Ta 1-x )2O5 solid solution exhibits excellent dielectric properties and high temperature stability in high-performance dielectric material applications.
[0006] At present, the preparation of (Nb x Ta 1-x )2O5 oxide solid solution is mainly prepared by atomic layer deposition and vapor deposition. Kukli et al. 1-x Nb x )2O5solidsolution films and Ta2O5-Nb2O5nanolaminates" were prepared by atomic layer deposition (Nb x Ta 1-x )2O5 solid solution film. Metal precursors Ta(OC2H5)5 or TaCl5 and Nb(OC2H5)5 were used as raw materials, and ethanol and water were used as oxidants. The deposition temperature was set at 300°C to 325°C, and the reactor pressure was about 10 mbar. By adjusting the deposition cycle ratio of Nb2O5 to Ta2O5 (from 2:7 to 15:3) and controlling the Nb / Ta content in the film, (Nb2O5) with a thickness of more than 200 nm was finally obtained. x Ta 1-x)2O5 solid solution nanolayer film, ensuring the uniformity and stability of its structure. x Ta 1-x )2O5 thin films (25-33) are optimized with increasing niobium content, with the optimum niobium content being approximately 5-7%. x Ta 1-x )2O5 solid solution nanolayer films have high accuracy and uniformity, but their deposition rate is slow and the process is complicated. Matsui et al. synthesized (Nb2O5) by chemical vapor deposition (CVD) in the paper "Combining Ta2O5 and Nb2O5 in bilayered structures and solid solutions for use in mim capacitors". x Ta 1-x )2O5 solid solution. (Nb x Ta 1-x )2O5 thin films were deposited in a mixture of argon and oxygen at a deposition temperature of 300°C, an incident power of 50 W, a film thickness range of 5-50 nm, and a deposition rate of 1.8 nm / min. After film deposition, the film was heat treated in nitrogen (500°C to 800°C, 1 minute) and then oxidized in oxygen (500°C, 2 minutes). The study found that when (Nb x Ta 1-x )2O5 solid solution contains more than 90% Nb2O5, the dielectric constant is greater than 60, showing higher dielectric properties. x Ta 1-x )2O5 solid solution leakage current at low voltage is similar to that of pure Ta2O5 (10 -7 A / cm 2 ) and showed excellent leakage current suppression performance. However, the preparation process is cumbersome, and the experiment involves a variety of materials and equipment, which requires high maintenance and operation of the equipment. In addition, controlling the deposition conditions of different materials and optimizing different processing steps may require additional time and cost.
[0007] In summary, (Nb x Ta 1-x )2O5 oxide solid solution has attracted wide attention in adjustable dielectric capacitors and different application scenarios due to its excellent dielectric properties. To this end, the present invention provides a (Nb x Ta 1-x )2O5 oxide solid solution preparation method. This method uses (Nb,Ta)(C,N) as a precursor and directly prepares (Nb x Ta 1-x)2O5 oxide solid solution. This preparation technology not only simplifies the production process and reduces energy consumption, but also avoids the use of organic solvents, thereby significantly improving environmental protection and production safety. In addition, the simplicity of this method also makes mass production possible, further improving the feasibility of industrial application. (Nb x Ta 1-x )2O5 oxide solid solution shows broad application prospects in high temperature resistant, high voltage resistant and adjustable dielectric capacitors and different application scenarios. Summary of the invention
[0008] In order to solve the problems of high temperature phase stability, high voltage breakdown resistance and dielectric constant adjustability of dielectric capacitor materials. x Ta 1-x )2O5 powder preparation method, using (Nb,Ta)(C,N) carbonitride powder as raw material, through a one-step oxidation method, successfully prepared (Nb x Ta 1-x )2O5 powder. Its technical route mainly includes the following two steps:
[0009] (I) (Nb x Ta 1-x )(C y N 1-y ) (where x ranges from 0.1 to 0.6, and y ranges from 0.78 to 0.86) carbonitride is used as a precursor. The precursor is placed in a furnace, heated to 1000℃-1500℃ at a heating rate of 2-10℃ / min by a one-step oxidation method in an air atmosphere, and kept at this temperature for 0.5-10 hours to perform an oxidation reaction. After the reaction is completed, the product is cooled to room temperature with the furnace, thereby obtaining (Nb x Ta 1-x )2O5 oxide solid solution powder.
[0010] (II) The preparation process of (Nb,Ta)(C,N) precursor is as follows: NbC and TaC powders are used as raw materials, and metal Co powder is used as flux; (1) NbC and TaC powders are weighed according to the required molar ratio (0.11-1.5):1, while ensuring that the total mass of carbide and the mass ratio of metal Co is 3:7, and they are mixed evenly; (2) The mixed powder is pressed into a shape and placed in a furnace, and heated to 1500℃-1900℃ at a heating rate of 5-10℃ / min under a nitrogen environment, and kept warm for 0.5-6 hours. After the heat treatment, the product is cooled to room temperature with the furnace to obtain a (Nb,Ta)(C,N) / Co metal-based ceramic block; (3) The obtained ceramic block is immersed in a dilute nitric acid solution to remove the Co alloy matrix; (4) After filtering, washing and drying, (Nb,Ta)(C,N) carbonitride powder is obtained.
[0011] The working principle of the present invention is: the selected carbonitride raw material is (Nb x Ta 1-x )(C y N 1-y ) (x=0.1~0.6, y=0.78~0.86), the material presents a rock salt (NaCl) type crystal structure and belongs to the space group Fm3m. In this structure, Nb and Ta atoms are located at the vertices and body center of the lattice, respectively, while C and N atoms are located at the midpoints along the edges and the center of the face. This atomic arrangement causes each Nb and Ta atom to be surrounded by six C or N atoms, forming an octahedral coordination structure; at the same time, each C or N atom is also surrounded by six Nb and Ta atoms, forming a dense octahedral coordination environment. This arrangement promotes the common diffusion of Nb and Ta atoms, thereby improving the uniformity and efficiency of the oxidation reaction. During the oxidation process, due to the dense octahedral coordination crystal structure, the Nb and Ta atoms have a shorter migration distance, the reaction rate is accelerated, so the entire oxidation process can be completed in a shorter time, thereby improving the preparation efficiency and reducing energy consumption. In addition, when x is in the range of 0.1~0.6, the transformation of orthorhombic Nb2O5 to monoclinic Nb2O5 is inhibited, and the (Nb x Ta 1-x )2O5 is an orthorhombic crystal structure. Therefore, the present invention uses (Nb, Ta) (C, N) carbonitride as a precursor to achieve a simplified preparation process, which can effectively promote the uniform reaction of oxygen atoms with Nb and Ta atoms in the crystal structure, and finally form (Nb x Ta 1-x )2O5 oxide. Compared with the traditional atomic layer deposition method and vapor deposition method, it has significant advantages. Although the above two processes can prepare (Nb x Ta 1-x )2O5 solid solution, but these two methods have slow deposition rates and complex process flows, which can easily lead to uneven composition and defects in the prepared solid solution. On the contrary, the method of the present invention uses (Nb, Ta)(C, N) precursors, which effectively ensures the uniformity of the elements and ensures that the generated (Nb x Ta 1-x )2O5 solid solution is single phase and the elements are evenly distributed. At the same time, this method significantly shortens the production cycle and simplifies the production process, showing its great application potential in industrial production.
[0012] The present invention has the following advantages:
[0013] (1) The preparation process of the present invention is considered to be simple, with a short preparation cycle and energy saving; no organic solvent is used, safety and environmental protection are guaranteed, and conditions are provided for industrial-scale production.
[0014] (2) The (Nb x Ta 1-x )2O5 is considered to be a dielectric material that is resistant to high temperature and high voltage breakdown and has high adjustability. These properties make it an ideal dielectric capacitor material, showing great potential in high-performance applications.
[0015] The present invention has the following advantages:
[0016] (1) The preparation process of the present invention is considered to be simple, the preparation cycle is considered to be short, and energy is saved; organic solvents are not used, safety and environmental protection are guaranteed, and conditions are provided for industrial-scale production.
[0017] (2) The (Nb x Ta 1-x )2O5 is considered to be a dielectric material that is resistant to high temperature and high voltage breakdown and has high adjustability. These properties make it an ideal dielectric capacitor material, showing great potential in high-performance applications. Example
[0018] Figure 1 is the (Nb prepared in Example 1 0.1 Ta 0.9 )XRD image of 2O5 powder.
[0019] Figure 2 is the (Nb prepared in Example 2 0.2 Ta 0.8 )XRD image of 2O5 powder.
[0020] Figure 3 is the (Nb prepared in Example 2 0.2 Ta 0.8 )SEM image of 2O5 powder.
[0021] Figure 4 is the (Nb prepared in Example 3 0.3 Ta 0.7 )XRD image of 2O5 powder.
[0022] Figure 5 is prepared in Example 4 (Nb 0.4 Ta 0.6 )XRD image of 2O5 powder.
[0023] Figure 6 is the (Nb prepared in Example 5 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0024] Figure 7 is the (Nb prepared in Example 5 0.5 Ta 0.5 )SEM image of 2O5 powder.
[0025] Figure 8 is prepared in Example 6 (Nb 0.6 Ta 0.4 )XRD image of 2O5 powder.
[0026] Fig. 9 is prepared in Example 6 (Nb 0.6 Ta 0.4 )EDS image of 2O5 powder.
[0027] Fig.10 is prepared in Example 7 (Nb 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0028] Fig.11 is prepared in Example 8 (Nb 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0029] Fig.12 is prepared in Example 8 (Nb 0.5 Ta 0.5 )SEM image of 2O5 powder.
[0030] Fig.13 is prepared in Example 9 (Nb 0.2 Ta 0.8 )XRD image of 2O5 powder.
[0031] Fig.14 is prepared in Example 9 (Nb 0.2 Ta 0.8 )XRD image of 2O5 powder.
[0032] Fig.15 is the (Nb prepared in Example 10 0.4 Ta 0.6 )XRD image of 2O5 powder.
[0033] Fig.16 is the (Nb prepared in Example 11 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0034] Fig.17 is the (Nb prepared in Example 11 0.5 Ta 0.5)SEM image of 2O5 powder.
[0035] Fig.18 is the (Nb prepared in Example 12 0.6 Ta 0.4 )XRD image of 2O5 powder.
[0036] Fig.19 is the (Nb prepared in Example 13 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0037] Fig. 20 is the (Nb prepared in Example 14 0.5 Ta 0.5 )XRD image of 2O5 powder.
[0038] Fig.21 is the (Nb prepared in Example 14 0.5 Ta 0.5 )SEM image of 2O5 powder.
[0039] Example 1
[0040] In this embodiment, (Nb 0.1 Ta 0.9 )2O5 powder is prepared as follows: 0.1 Ta 0.9 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.1 Ta 0.9 )2O5 powder.
[0041] The (Nb 0.1 Ta 0.9 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:9, keep the total mass of carbide and the mass of Co powder at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.1 Ta 0.9 )(C 0.78 N 0.22) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.1 Ta 0.9 )(C 0.78 N 0.22 )Carbonitride powder.
[0042] The prepared (Nb 0.1 Ta 0.9 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 1 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.1 Ta 0.9 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.82°, 28.26° and 36.64°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.1 Ta 0.9 )2O5 oxide solid solution and has good crystallinity.
[0043] Example 2
[0044] In this embodiment, (Nb 0.2 Ta 0.8 )2O5 powder is prepared as follows: 0.2 Ta 0.8 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.2 Ta 0.8 )2O5 powder.
[0045] The (Nb 0.2 Ta 0.8 )(C 0.78 N 0.22) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:4, keep the total mass of carbide and the mass of Co powder at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.2 Ta 0.8 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.2 Ta 0.8 )(C 0.78 N 0.22 )Carbonitride powder.
[0046] The prepared (Nb 0.2 Ta 0.8 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 2 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.2 Ta 0.8 )2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.86°, 28.38° and 36.72°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.2 Ta 0.8 )2O5 oxide solid solution and has good crystallinity.
[0047] The prepared (Nb 0.2 Ta 0.8 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Figure 3 shown. Figure 3 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 3 to 15 μm; Figure 3 (b) further shows that these triangular pyramids are composed of dense (Nb 0.2 Ta 0.8 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 0.5 to 2 µm.
[0048] Example 3
[0049] In this embodiment, (Nb 0.3 Ta 0.7 )2O5 powder is prepared as follows: 0.3 Ta 0.7 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.3 Ta 0.7 )2O5 powder.
[0050] The (Nb 0.3 Ta 0.7 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 3:7, keep the total mass of carbide and the mass of Co powder at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.3 Ta 0.7 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.3 Ta 0.7 )(C 0.78 N 0.22 )Carbonitride powder.
[0051] The prepared (Nb 0.3 Ta 0.7 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 4 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.1 Ta 0.9)2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.76°, 28.28° and 36.66°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.3 Ta 0.7 )2O5 oxide solid solution and has good crystallinity.
[0052] Example 4
[0053] In this embodiment, (Nb 0.4 Ta 0.6 )2O5 powder is prepared as follows: 0.4 Ta 0.6 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.4 Ta 0.6 )2O5 powder.
[0054] The (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 2:3, make the total mass of carbide and Co powder mass maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 )Carbonitride powder.
[0055] The prepared (Nb 0.4 Ta 0.6 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 5Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.4 Ta 0.6 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.82°, 28.38° and 36.72°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.4 Ta 0.6 )2O5 oxide solid solution and has good crystallinity.
[0056] Example 5
[0057] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0058] The (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, the total mass of carbide and the mass of Co powder are kept at 3:7, and fully mix; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 )Carbonitride powder.
[0059] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 6 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta 0.5 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.72°, 28.32° and 36.62°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.5 Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0060] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Figure 7 shown. Figure 7 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 5 to 11 µm; Figure 7 (b) further shows that these triangular pyramids are composed of dense (Nb 0.5 Ta 0.5 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 1.5 to 3.5 µm.
[0061] Example 6
[0062] In this embodiment, (Nb 0.6 Ta 0.4 )2O5 powder is prepared as follows: 0.6 Ta 0.4 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.6 Ta 0.4 )2O5 powder.
[0063] The (Nb 0.6 Ta 0.4 )(C 0.78 N 0.22) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 3:2, make the total mass of carbide and Co powder mass maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.6 Ta 0.4 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.6 Ta 0.4 )(C 0.78 N 0.22 )Carbonitride powder.
[0064] The prepared (Nb 0.6 Ta 0.4 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Figure 8 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.6 Ta 0.4 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.82°, 28.38° and 36.68°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.6 Ta 0.4 )2O5 oxide solid solution and has good crystallinity.
[0065] The energy dispersive spectrometer (Nb) on the scanning electron microscope was used to analyze the 0.6 Ta 0.4 )2O5 powder was subjected to energy dispersive X-ray spectroscopy (EDS) point analysis, such as Fig. 9 EDS results show that the oxidation product contains Nb, Ta and O elements, and the Nb / Ta ratio is 1.66:1, which is close to the pre-designed ratio, achieving controllable composition and further confirming that the prepared sample is (Nb 0.6 Ta 0.4 )2O5 powder.
[0066] Example 7
[0067] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.84 N 0.16 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0068] The (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, the total mass of carbide and the mass of Co powder are kept at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1700℃ at a rate of 10℃ / min in a nitrogen atmosphere for 1 hour. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 )Carbonitride powder.
[0069] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.10 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta 0.5 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.74°, 28.32° and 36.62°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb0.5 Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0070] Example 8
[0071] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.86 N 0.14 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1200°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0072] The (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, make the total mass of carbide and the mass of Co powder maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1900℃ at a rate of 10℃ / min in a nitrogen atmosphere, and keep it at this temperature for 0.5 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14 )Carbonitride powder.
[0073] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.11 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta0.5 )2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.76°, 28.32° and 36.62°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.5 Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0074] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Fig.12 shown. Fig.12 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 10 to 25 µm; Fig.12 (b) further shows that these triangular pyramids are composed of dense (Nb 0.5 Ta 0.5 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 1.5 to 4 µm.
[0075] Example 9
[0076] In this embodiment, (Nb 0.2 Ta 0.8 )2O5 powder is prepared as follows: 0.2 Ta 0.8 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.2 Ta 0.8 )2O5 powder.
[0077] The (Nb 0.2 Ta 0.8 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:4, keep the total mass of carbide and the mass of Co powder at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.2 Ta 0.8 )(C 0.78N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.2 Ta 0.8 )(C 0.78 N 0.22 )Carbonitride powder.
[0078] The prepared (Nb 0.2 Ta 0.8 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.13 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.2 Ta 0.8 )2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.86°, 28.34° and 36.68°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.2 Ta 0.8 )2O5 oxide solid solution and has good crystallinity.
[0079] The prepared (Nb 0.2 Ta 0.8 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Fig.14 shown. Fig.14 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 5 to 15 µm; Fig.14 (b) further shows that these triangular pyramids are composed of dense (Nb 0.2 Ta 0.8 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 0.1 to 0.5µm.
[0080] Example 10
[0081] In this embodiment, (Nb 0.4 Ta 0.6 )2O5 powder is prepared as follows: 0.4 Ta 0.6 )(C 0.78 N 0.22) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.4 Ta 0.6 )2O5 powder.
[0082] The (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 2:3, make the total mass of carbide and Co powder mass maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.4 Ta 0.6 )(C 0.78 N 0.22 )Carbonitride powder.
[0083] The prepared (Nb 0.4 Ta 0.6 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.15 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.4 Ta 0.6 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.80°, 28.34° and 36.68°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.4 Ta 0.6 )2O5 oxide solid solution and has good crystallinity.
[0084] Embodiment 11
[0085] In this embodiment, (Nb0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0086] The (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, the total mass of carbide and the mass of Co powder are kept at 3:7, and fully mix; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 )Carbonitride powder.
[0087] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.16 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta 0.5 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.78°, 28.34° and 36.66°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.5Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0088] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Fig.17 shown. Fig.17 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 3 to 22 μm; Fig.17 (b) further shows that these triangular pyramids are composed of dense (Nb 0.5 Ta 0.5 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 0.2 to 1 µm.
[0089] Example 12
[0090] In this embodiment, (Nb 0.6 Ta 0.4 )2O5 powder is prepared as follows: 0.6 Ta 0.4 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.6 Ta 0.4 )2O5 powder.
[0091] The (Nb 0.6 Ta 0.4 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 3:2, make the total mass of carbide and Co powder mass maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1500℃ at a rate of 5℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.6 Ta 0.4 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.6 Ta 0.4)(C 0.78 N 0.22 )Carbonitride powder.
[0092] The prepared (Nb 0.6 Ta 0.4 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.18 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.6 Ta 0.4 )2O5 solid solution and orthorhombic phase. In particular, the three strong peaks are located at 22.76°, 28.36° and 36.62°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.6 Ta 0.4 )2O5 oxide solid solution and has good crystallinity.
[0093] Embodiment 13
[0094] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.84 N 0.16 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0095] The (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, the total mass of carbide and the mass of Co powder are kept at 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into a shape, put it into a furnace, and heat it to 1700℃ at a rate of 10℃ / min in a nitrogen atmosphere for 1 hour. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 )Carbonitride powder.
[0096] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig.19 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta 0.5 )2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.82°, 28.36° and 36.72°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.5 Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0097] Embodiment 14
[0098] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.86 N 0.14 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1000°C at a rate of 5°C / min in an air atmosphere, and then kept warm for 2 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0099] The (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, make the total mass of carbide and the mass of Co powder maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1900℃ at a rate of 10℃ / min in a nitrogen atmosphere, and keep it at this temperature for 0.5 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.86 N 0.14 )Carbonitride powder.
[0100] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was subjected to X-ray diffraction (XRD) phase analysis, and the results are as follows Fig. 20 Each characteristic peak shows clear and sharp characteristics, and is between the characteristic peaks of orthorhombic Nb2O5 phase (JCPDS: 27-1003) and Ta2O5 (JCPDS: 25-0922), confirming that the product is (Nb 0.5 Ta 0.5 )2O5 solid solution and is an orthorhombic phase. In particular, the three strong peaks are located at 22.78°, 28.38° and 36.68°, corresponding to the (001), (180), and (181) crystal planes of Nb2O5, respectively. The above results prove that the (Nb 0.5 Ta 0.5 )2O5 oxide solid solution and has good crystallinity.
[0101] The prepared (Nb 0.5 Ta 0.5 )2O5 powder was characterized by scanning electron microscopy (SEM), and the results are as follows Fig.21 shown. Fig.21 (a) shows that the oxide solid solution presents a triangular pyramidal morphology, with the edge length ranging from 10 to 25 μm; Fig.21 (b) further shows that these triangular pyramids are composed of dense (Nb 0.5 Ta 0.5 )2O5 particles are sintered, with gaps between the particles and a particle size ranging from 0.1 to 1.5 µm.
[0102] Embodiment 15
[0103] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.78 N 0.22 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1500°C at a rate of 2°C / min in an air atmosphere, and then kept warm for 0.5 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb 0.5 Ta 0.5 )2O5 powder.
[0104] The (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, make the total mass of carbide and the mass of Co powder maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1500℃ at a rate of 8℃ / min in a nitrogen atmosphere for 6 hours. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.78 N 0.22 )Carbonitride powder.
[0105] Example 16
[0106] In this embodiment, (Nb 0.5 Ta 0.5 )2O5 powder is prepared as follows: 0.5 Ta 0.5 )(C 0.84 N 0.16 ) carbon nitride as the precursor. The precursor was placed in a furnace and heated to 1400°C at a rate of 10°C / min in an air atmosphere, and then kept warm for 10 hours to ensure full oxidation. After the reaction was completed, the product was naturally cooled to room temperature with the furnace to obtain (Nb0.5 Ta 0.5 )2O5 powder.
[0107] The (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 ) precursor preparation method is as follows: select NbC and TaC powder as raw materials, metal Co powder as flux; (1) accurately weigh NbC and TaC powder, the molar ratio is 1:1, make the total mass of carbide and Co powder mass maintain 3:7, and mix them thoroughly; (2) use a mold to press the mixed powder into shape, put it into a furnace, and heat it to 1700℃ at a rate of 8℃ / min in a nitrogen atmosphere, and keep it at this temperature for 1 hour. After heat treatment, the product is naturally cooled to room temperature in the furnace to form (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 ) / Co metal-based ceramic block; (3) immersing the obtained ceramic block in a dilute nitric acid solution to dissolve and corrode the Co alloy matrix; (4) after the corrosion is completed, filtering the remaining product, washing it multiple times, and drying it to obtain (Nb 0.5 Ta 0.5 )(C 0.84 N 0.16 )Carbonitride powder.
Claims
1. A method for preparing (Nb x Ta 1-x )2O5 oxide solid solution powder, characterized in that: With (Nb x Ta 1-x )(C y N 1-y ) (where x ranges from 0.1 to 0.6, and y ranges from 0.78 to 0.86) carbonitride is used as a precursor. The precursor is placed in a furnace, heated to 1000℃-1500℃ at a heating rate of 2-10℃ / min by a one-step oxidation method in an air atmosphere, and kept at this temperature for 0.5-10 hours to perform an oxidation reaction. After the reaction is completed, the product is cooled to room temperature with the furnace, thereby obtaining (Nb x Ta 1-x )2O5 oxide solid solution powder.
2. The method according to claim 1, wherein the preparation process of (Nb, Ta) (C, N) powder is as follows: NbC and TaC powders are used as raw materials, and metal Co powder is used as flux; (1) NbC and TaC powders are weighed according to the required molar ratio (0.11-1.5):1, while ensuring that the total mass of carbide and the mass ratio of metal Co is 3:7, and they are mixed evenly; (2) The mixed powder is pressed into a shape and placed in a furnace, and heated to 1500-1900°C at a heating rate of 5 to 10°C / min under a nitrogen environment, and kept warm for 0.5-6 hours. After the heat treatment is completed, the product is cooled to room temperature with the furnace to obtain a (Nb, Ta) (C, N) / Co metal-based ceramic block; (3) The obtained ceramic block is immersed in a dilute nitric acid solution to remove the Co alloy matrix; (4) After filtering, washing and drying, (Nb, Ta) (C, N) carbonitride powder is obtained.